Social support and its influencing factors among grassroots medical staff: an online cross-sectional survey in Zhejiang province - Feifei GUO; Chenwei HOU; Qimei WANG; Junfen LIN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo study social support and its influencing factors among grassroots medical staff in Zhejiang province for developing relevant interventions. MethodsAn online anonymous questionnaire survey was conducted among 2 122 conveniently recruited frontline medical staff in community health centers/township hospitals in 11 prefectures across Zhejiang province from December 2022 to January 2023. The Social Support Scale (SSRS) developed by Chinese researchers was used in the survey. Multivariate linear regression was adopted to analyze influencing factors of social support in the participants. ResultsFor the 1 803 participants with valid responses, the total score of social support was 40.17 ± 8.49, with the subjective support score of 23.18 ± 5.34, objective support score of 9.48 ± 3.09, and social support utilization score of 7.51 ± 1.98. Multivariate linear regression analysis showed that for the grassroots medical personnel, work years, daily sleep time, annual income, and marital status were significant influencing factors of general, subjective, and objective social support (all P < 0.05) and gender, daily sleep time, annual income, and marital status were significant factors affecting the utilization of social support (P < 0.05 for all). ConclusionThe perceived social support is generally good but the support is not effectively utilized among grassroots medical staff in Zhejiang province. Special attention should be paid to the social support for the staff having been working for 3 - 15 years, being unmarried, having daily sleep time of less than 7 hours, and with an annual income of less than 100 000 Chinese Yuan and to the utilization of social support in the male staff.